Effects of Muscle Energy Technique and Stretching Exercise on Pain, Hip Joint Range of Motion and Function in Working Pregnant Women with Piriformis Syndrome - NAEEM, SHAFAQ; TARIQ, MARIYA; ASLAM, JAVERIA; FATIMA, MAHNOOR; BUTT, AQSA; GULL, MASOOMA; MUNEEB, HAFIZA NEELAM (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Piriformis syndrome is a neuromuscular disorder characterized by pain, paresthesia, and numbness in the gluteal region and along the distribution of the sciatic nerve. It is commonly managed using therapeutic interventions such as Muscle Energy Technique (MET). Objective: To determine the effects of muscle energy technique Efficacy of Therapeutic Exercise Protocols on Hip Range of Motion and Pain in Pregnant Women with Occupational Piriformis Syndrome Methods: A randomized clinical trial was conducted at THQ Kamoke, Gujranwala, with 28 participants selected through non-probability convenience sampling. After informed consent, participants were randomly assigned to either the MET group or the stretching exercise group. Interventions lasted eight weeks with three sessions per week. Outcomes were measured using the Numerical Pain Rating Scale (NPRS), Lower Extremity Functional Scale (LEFS), and a goniometer for hip internal rotation ROM. Pre- and post-intervention data were analyzed using SPSS 22. Results: Both groups showed significant improvements (p < 0.05) in pain, ROM, and function. NPRS scores improved from a mean of 6.27 to 0.14, LEFS from 0.14 to 6.13, and internal hip rotation ROM from 0.8 to 2.0. Post-intervention, stretching exercises showed slightly greater effectiveness than MET. Conclusion: The study found that stretching exercises and muscular energy techniques reduce pain, increase hip joint ROM and function in working pregnant women with piriformis syndrome. However, stretching exercise is more effective than muscle energy technique.